PWE-298 Ct usage for the detection of post-operative colorectal complications: impact on radiological and surgical services. (22nd June 2015) - Florance, CJ; Francis, R; Kynaston, J; Cook, TA
Abstract : Introduction: Detecting surgical complications early is a persistent challenge. The aim of this study was to evaluate the use of abdominal and pelvic computed tomography (CTAP) in postoperative colorectal patients, exploring the impact on subsequent clinical management and on hospital resources. Method: Data were collected on all patients undergoing elective colorectal surgery within an enhanced recovery programme over a two-year period (January 2011–December 2012). Those patients who had a diagnostic postoperative CTAP during their first admission were identified and their case notes analysed. Results: Three hundred and fifty patients were identified, of which 166 (47%) had undergone laparoscopic procedures. Thirty-nine patients (11%) had a total of 40 diagnostic postoperative CTAP scans. Of these, 15 (38%) had had laparoscopic operations. Median time to imaging was 8 days post-operation. Anastomotic leak was noted in 5 patients undergoing scans (13%); 2 had percutaneous drainage and 3 were managed conservatively with intravenous antibiotics. Collections were identified in 10 patients (25%) of which 1 patient returned to theatre, 3 had percutanous drainage and 6 were managed conservatively. Bowel obstruction was reported in 3 patients (7%) and paralytic ileus in 14 (37%). One patient had a second scan due to further clinical deterioration which suggested likely ischaemic bowel changes, resulting in a return to theatre. No intra-abdominal complications were reported in seven patients (18%). Three patients returned to theatre without any imaging. Conclusion: There was a high threshold for imaging colorectal patients in the postoperative period with 11% undergoing scans. There was no difference in the proportion undergoing scans between laparoscopic and open procedures. Septic pathology (leak or collection) was identified in a significant proportion (38%) but only 1.4% (5/350) of the overall number underwent radiological intervention. This study shows that CTAP is useful in detecting postoperative complications but has minimal impact on radiological services. Disclosure of interest: None Declared.